Evaluasi Penerapan Risk-Based Audit untuk Mendeteksi Ketidakpatuhan Akuntan Publik terhadap Standar Profesi dan Regulasi - Diky Mahendra; Agung Nugroho Soedibyo (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to evaluate the effectiveness of implementing risk-based audit to detect non- compliance of certified public accountants (CPAs) against professional standards and regulations. The research object in this study is Pusat Pembinaan Profesi Keuangan (PPPK), an authorized regulator to provide coaching and supervision of the public accounting profession. This research is motivated by the policy of redesigning the function of coaching and supervising the finance professions. One approach focuses on preparing CPAs risk profiles, which then become the basis for determining risk-based supervision patterns. In addition, there is an imbalance between the number of CPAs supervised and the number of resources owned by the regulator, so an effective supervision strategy is required through the risk-based audit approach. The research method used in this research is a descriptive qualitative method through semi- structured interviews, document analysis, and literature study. The results showed that the implementation of risk-based audit in PPPK was in line with current guidelines and regulations. The use of risk-based audit is effective in supporting PPPK to become more focus in detecting CPAs non-compliance against professional standards and regulations. However, in the implementation process, there are still issues related to the variables used to calculate the CPAs risk level, where qualitative information is an important factor in determining the selected inspection object. PPPK needs to improve the guidelines for preparing CPAs risk profiles so that the risk-based supervision function becomes more effective.